THE ROLE AND PLACE OF SMALL BUSINESS IN THE DEVELOPMENT OF THE SERVICE SECTOR IN UZBEKISTAN - Faizieva , Sayyora Kudratovna; Zakirova , Manzura Ilkhomovna (Educational Research in Universal Sciences, 2023)
This article describes the characteristics and role of small business in the development of the service sector on the example of foreign countries, the history of the emergence of small business, its need for employment. About attracting customers and the quality of service in the service sector.